Dermatoglyphs of Klinefelter's syndrome. - Shiono, H (1977)
The dermatoglyphs of 28 Japanese with Klinefelter's syndrome [24 XXY; 2 XXYY; 1 XXXY; 1 XXXXY] were compared with 544 male and 129 female controls. These patients showed high frequencies of fingertip arches pattern, right third interdigital loops, right hypothenar patterns (Lr) and line C terminating 0 in the right hand. The mean summed a-b ridge count of Klinefelter's syndrome patients was significantly lower than that of the male controls. We suggest that an increase in the number of X or Y chromosomes decreased the a-b ridge count in a similar way to the decrease in total finger ridge count.